2020
DOI: 10.1111/1365-2745.13369
|View full text |Cite
|
Sign up to set email alerts
|

The community‐level scaling relationship between leaf nitrogen and phosphorus changes with plant growth, climate and nutrient limitation

Abstract: 1. The scaling relationship between the concentrations of leaf nitrogen (N) and phosphorus (P), which can be formulated as [N] = α[P] β , shows the relative investment of plants in nutrient uptake. Most of the current knowledge on this topic is based on studies at the individual or species level. However, patterns at these levels can hardly reflect the response of vegetation or ecosystems along environmental gradients. 2. Here, we explored how the nutrient demands of vegetation as a whole vary with productivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 57 publications
1
12
0
2
Order By: Relevance
“…Therefore, in the desert with less precipitation, longer dry-period, and deficient soil nutrient in Central Asia, in order to complete their life cycle in a short time (generally less than two months), ephemeral plants must retain high N concentration in their leaves to cope with environmental stress and retain high P allocation rate to maintain normal physiological metabolism and growth. These results well confirm the environmental stress-growth rate hypothesis (Ågren and Weih 2020;Guo et al 2020;Tian et al 2018;Wang et al 2019a).…”
Section: Relationships Of N P and N:p In Leaves And Roots In Desert Areassupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, in the desert with less precipitation, longer dry-period, and deficient soil nutrient in Central Asia, in order to complete their life cycle in a short time (generally less than two months), ephemeral plants must retain high N concentration in their leaves to cope with environmental stress and retain high P allocation rate to maintain normal physiological metabolism and growth. These results well confirm the environmental stress-growth rate hypothesis (Ågren and Weih 2020;Guo et al 2020;Tian et al 2018;Wang et al 2019a).…”
Section: Relationships Of N P and N:p In Leaves And Roots In Desert Areassupporting
confidence: 86%
“…and vegetation types. It is generally believed that relatively strong environmental stress leads to the decrease of growth rate and the increase of N-P scaling exponent; on the contrary, if plants do not feel stress, their growth rate will be faster, resulting in low N-P scaling exponent (Ågren and Weih 2020;Guo et al 2020;Tian et al 2018;Wang et al 2019a). This result suggests that low N-P scaling exponent of ephemeral plants is consistent with their rapid growth.…”
Section: Relationships Of N P and N:p In Leaves And Roots In Desert Areasmentioning
confidence: 99%
“…LDMC indicates the leaf water content, storage capacity and strategies for distributing nutrients and substances (Hodgson et al 2011). N and P are important elements that affect plant metabolism, energy transmission and ecological processes (Abdala- Roberts et al 2018;Guo et al 2020).…”
Section: Leaf Trait Measurementsmentioning
confidence: 99%
“…It was reported that the strong stoichiometric relationships between plant nutrients and their ratios could be quantified by a power function as i = βj α , where i and j indicate plant nutrient concentrations and their ratios, respectively; α and β indicate the scaling exponent and normalization constant, which are the slope and the "elevation" or Y-intercept of the log-log linear i vs. j regression line, respectively (Wright et al, 2004;Reich et al, 2010;Tian et al, 2018). The scaling exponent α was widely applied to quantified the stoichiometric relationship between N and P across species under multiple nutrient environments (Tian et al, 2019;Guo et al, 2020;Zhao et al, 2021). However, limited studies focus on the scaling exponent related to C and K.…”
Section: Introductionmentioning
confidence: 99%